2017
DOI: 10.1088/1361-665x/aa6a93
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive acoustic energy delivery to near and far fields using foldable, tessellated star transducers

Abstract: Methods of guiding acoustic energy arbitrarily through space have long relied on digital controls to meet performance needs. Yet, more recent attention to adaptive structures with unique spatial configurations has motivated mechanical signal processing (MSP) concepts that may not be subjected to the same functional and performance limitations as digital acoustic beamforming counterparts. The periodicity of repeatable structural reconfiguration enabled by origami-inspired tessellated architectures turns attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In [31] far-field time reversal was used to overcome those challenges. Another approach is the smart design of transducers with adaptive structures such as classical rectangular panels in an infinite baffle [42], foldable tessellated star transducers [53], Helmholtz resonators with computerized controls [30] and modern metamaterials [49].…”
Section: Introductionmentioning
confidence: 99%
“…In [31] far-field time reversal was used to overcome those challenges. Another approach is the smart design of transducers with adaptive structures such as classical rectangular panels in an infinite baffle [42], foldable tessellated star transducers [53], Helmholtz resonators with computerized controls [30] and modern metamaterials [49].…”
Section: Introductionmentioning
confidence: 99%
“…Where rms is the root mean square value of p ( x , y , z , t ) and the reference pressure in air is p ref = 20 μ Pa and in water is p ref = 1 μ Pa . These modeling approaches for shaped acoustic transducers are widely used and verified for their efficacy in model prediction (Ebbini and Cain, 1991; Jensen and Svendsen, 1992; Ross et al, 2005; Wan et al, 1996; Zou and Harne, 2017).…”
Section: Model Formulationmentioning
confidence: 99%
“…For instance, tessellated water-bomb and star-based arrays of acoustic transducers studied by Lynd et al (2017) and Zou et al (2018) have wave guiding properties in the near and far field in addition to the ability to fold into compact shapes for transport. Moreover, the reconfiguration of such origami-inspired acoustic arrays empowers means to control interference phenomena and thus modulate the wave guiding properties (Lynd and Harne, 2017; Zou et al, 2018; Zou and Harne, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these arrays have portability challenges due to their size and construction, nor are they reconfigurable to optimize transducer placement for varying frequencies. Recently, Zou and Harne (2017) have shown that tessellated star origami functions as a reconfigurable and portable wave guiding array where the tessellated star facets are assumed to be vibrating baffled pistons that radiate acoustic pressure.…”
Section: Introductionmentioning
confidence: 99%